A nanocrystal-based formulation improves the pharmacokinetic performance and therapeutic response of albendazole in dogs - Paredes, Alejandro Javier (2018)
We aimed to assess the pharmacokinetic performance and therapeutic response (anthelmintic efficacy) of an albendazole (ABZ) nano-sized formulation in dogs. Methods: In the pharmacokinetic study, ABZ self-dispersible nanocrystals (SDNCS) and a control formulation were administered orally to healthy dogs (n = 6). The concentrations of the sulphoxide metabolite in plasma were determined by high-performance liquid chromatography. For the anthelmintic efficacy trial, SDNCS and a commercially available formulation of ABZ were given to naturally parasitised dogs. The number of Ancylostoma caninum eggs in the faeces was determined using the McMaster technique. Key findings: The area under the curve, Tmax and Cmax for the SDNCS were improved compared to the control. The efficacy study showed no statistical differences between the SDNCS and the commercial formulation at the doses of 25 and 12.5 mg/kg. However, significant differences (P < 0.05) between the treatments were found at 6.25 mg/kg (a quarter of the reference dose) with a reduction in the faecal nematode egg counts of 62.0 ± 21.1% and 100 ± 0% for the control and SDNCS, respectively. Conclusions: The improved pharmacokinetic performance observed for the novel formulation of ABZ correlated with an improved in vivo therapeutic response against a model intestinal nematode parasite in dogs.